Evaluating The Effect Of Deterioration On The Engine Performance And Its Emissions Running On Alternative Fuels - Maniam, Senebahven (Universiti Sains Malaysia, 2018)
The need and the ability to obtain fast as well as reliable global transportation are increasing from time to time. This has set new ground-breaking standards in the aviation industry while creating new challenges along the way in the field of science and technology. As a result of this, the consequences on climate change and on the environment are of huge concern and must be addressed at all levels in the aviation industry. In addition to this, the presence of deterioration will significantly affect the environment and the aviation industry. Hence, these would serve as the purpose of the research work that is being conducted. The research would compromise on investigations with regards to the effect of deterioration on the engine performance and its emission for a complete flight trajectory. The performance of bio-jet fuels on a deteriorated engine for a complete flight trajectory and the emissions emitted will also be investigated in this research. In order to be able to provide significant results, a commercially available test subject is researched. Hence, the CFM56-3 turbofan engine is chosen. The CFM56-3 is a two-spool high bypass ratio turbofan engine. It is commercially known since it is widely used on the Airbus A320 family as well as on the Boeing 737. The existence of previous flight models and data were used to validate the present research model. Jatropha Bio-synthetic Paraffinic Kerosene (JSPK), Camelina Bio-synthetic Paraffinic Kerosene (CSPK) and their blends with Jet-A are bio-jet fuels chosen as part of this research study. The deterioration rate is applied to all components within the CFM56-3 turbofan engine configuration in terms of delta efficiency. The magnitude of deterioration rate was done based on the data obtained from literature review. The parameters that are studied include the effect of the fuels on Thrust Specific Fuel Consumption (TSFC), Thrust as well as Turbine entry Temperature (TET). In terms of emissions, the emissions that will be studied in this study include Nitrogen Oxide (NOX) and Carbon Monoxide (COX).